A highly sensitive plasma-based amyloid-β detection system through medium-changing and noise cancellation system for early diagnosis of the Alzheimer’s disease - Yong Kyoung Yoo (Nature Portfolio, 2017)
Abstract We developed an interdigitated microelectrode (IME) sensor system for blood-based Alzheimer’s disease (AD) diagnosis based on impedimetric detection of amyloid-β (Aβ) protein, which is a representative candidate biomarker for AD. The IME sensing device was fabricated using a surface micromachining process. For highly sensitive detection of several tens to hundreds of picogram/mL of Aβ in blood, medium change from plasma to PBS buffer was utilized with signal cancellation and amplification processing (SCAP) system. The system demonstrated approximately 100-folds higher sensitivity according to the concentrations. A robust antibody-immobilization process was used for stability during medium change. Selectivity of the reaction due to the affinity of Aβ to the antibody and the sensitivity according to the concentration of Aβ were also demonstrated. Considering these basic characteristics of the IME sensor system, the medium change was optimized in relation to the absolute value of impedance change and differentiated impedance changes for real plasma based Aβ detection. Finally, the detection of Aβ levels in transgenic and wild-type mouse plasma samples was accomplished with the designed sensor system and the medium-changing method. The results confirmed the potential of this system to discriminate between patients and healthy controls, which would enable blood-based AD diagnosis.